Asthma and Other Respiratory Diseases of Children in Relation to Personal Behavior, Household, Parental and Environmental Factors in West China - Changan Cao; Yuna Wang; Li Peng; Weiqi Wu; Huimin Yang; Zhigang Li (Toxics, 2023)
Asthma and other respiratory diseases, which are of great concern in public health, are paid less attention in areas that are less economically developed. This research aimed to study the prevalence of critical respiratory diseases of children living in West China and figure out the potential influencing factors. A total of 575 children under the age of 14 were recruited from Xinjiang, China, to participate in the study in 2022. Information on activity patterns, socioeconomic and parental factors, and household and surrounding environment situations was obtained using a questionnaire survey. Logistic regression models were applied to estimate the odds ratios of respiratory disease prevalence in relation to behavior patterns, household, parental and environmental factors, respectively. The prevalence of ever doctor-diagnosed asthma, doctor-diagnosed bronchitis and current bronchitis were 4.7%, 19.0% and 14.4%, respectively. The prevalence of doctor-diagnosed pneumonia was 8.2%, which was two times higher in urban than rural areas. Longer annual heating duration was significantly associated with higher risks in children’s asthma and bronchitis, with an odds ratio (OR) and 95% confidence interval (95% CI) of 3.363 (95% CI: 1.215–9.298) and 1.267 (95% CI: 1.002–1.601), respectively. Opening the window longer in autumn would lead to higher risks of bronchitis, with ORs of 1.165 and 1.133, respectively, for doctor-diagnosed bronchitis and current bronchitis. Residential air pollution and having a residence close to waste incineration plant or garbage station were, respectively, significantly associated with higher risks of doctor-diagnosed bronchitis and asthma. Parental disease history was associated with a higher prevalence of children’s asthma and respiratory diseases, whereas breastfeeding and doing physical exercise were, respectively, significantly associated with a lower risk of asthma. A high prevalence of respiratory diseases in children in West China may be partly attributed to longer annual heating time, opening windows longer in autumn, surrounding environmental pollution, as well as parental disease history, whereas promoting physical activity and breastfeeding could be an effective measure to reduce the risk of childhood asthma in West China.